Socio-spatial modelling of social services for older adults in Portugal: Implications for social work practice in an aging world - Álvarez-Pérez, P.; Relinque-Medina, F.; Pena, M. J. (Journal of Gerontological Social Work)
Urbanization and an aging population challenges social service accessibility for older adults in Portugal. This study used socio-spatial modeling, integrating data from the Portuguese Social Charter and National Institute of Statistics, to evaluate service allocation and the mismatch with older adults’ needs. Geospatial and Multiple Linear Regression Models showed high demand and service saturation in urban centers like Lisbon, Porto, and Faro. Conversely, significant service gaps were identified in rural and inland regions. Lower utilization in economically weaker areas suggests a strong need for financial support. Findings suggest targeted regional planning for equitable resource allocation and better service provision.